Psychometric Properties of the Spanish Version of the Goal Orientation Scales in Ecuadorian Undergraduate Students - Barreno, Segundo Napoleón; Veas, Alejandro; Navas, Leandro; Castejón, Juan Luis (Frontiers in Psychology, 2020)
The present study aims to analyze the psychometric properties of the Goal orientation Scales (GOS; Skaalvic, 1997) in a sample of 2,170 Ecuadorian undergraduate students (M = 21.97, SD = 3.61; 61.6% female). The Exploratory Factor Analysis and Confirmatory Factor Analysis supported the four-factor structure of the GOS, and the scale exhibited an adequate factorial invariance for gender. The multidimensional Rasch analysis revealed that one item showed misfit, and the distribution of items did not correspond well with the levels of achievement goals. The current research addresses a formal gap related to the validation of the GOS in a Latin American country and provides advanced psychometric information to further improve the scale for its application to Spanish-speaking samples.